A framework for the design of computer‐assisted simulation training for complex police situations. Issue 4 (2014) - ,; ,; ,; ,
Abstract : Purpose – The purpose of this paper is to report progress concerning the design of a computer‐assisted simulation training (CAST) platform for developing decision‐making skills in police students. The overarching aim is to outline a theoretical framework for the design of CAST to facilitate police students' development of search techniques in complex interactions within the built environment, learning to apply and perform the five "quick peek" techniques for information gathering, and subsequent risk evaluation.Design/methodology/approach – The paper draws on Luckin's ecology of resources model of learner context informed with perspectives on reflective thinking from John Dewey and Donald Schön. The paper discusses design issues within the ecology of resources model applied on CAST for complex police situations.Findings – It is suggested that Luckin's framework with its focus on the interaction between different elements and filters in the learner's context together with Schön's perspective on reflection challenge educational designers to look beyond the immediate development of specific tools (such as the CAST in this project) and examine how these tools will be effectively embedded in the overall learning experience.Originality/value – This paper has presented two theoretical perspectives, Luckin's ecology of resources model and Schön's perspective on reflective practice as foundations for the educational design of CAST. Applying Luckin's framework as informed by Schön helps focus attention on issues that are important in the design process in order to facilitate educational transfer.